Application of the Contextual Teaching and Learning (CTL) Model to the Learning Outcomes of Pancasila Education in Grade IV Students - Simbolon, Elsa Lusiana; Pandra, Viktor; Abadi, Candres (Civiliza Publishing, Indonesia., 2025)
Education is a very important thing in human life, therefore humans cannot be separated from education, where with education humans will be more advanced in their civilization and more civilized in their social life. This study aims to determine the completeness of Pancasila Education learning outcomes after the application of the Contextual Teaching and Learning (CTL) learning model in Pancasila Education learning for fourth-grade students of SD Negeri 21 Lubuklinggau. This type of research is an experiment with a One Group Pre-test and Post-test design. In this study, one sample class was used, namely fourth grade with a total of 22 students. This means that all members of the population were sampled, the sampling technique was carried out using a saturated sampling technique. The instrument used by the researcher was in the form of 24 multiple-choice questions. Data collection was taken using a test. Data were analyzed using the z-test formula. Based on the results of the data analysis test with a confidence level of α = 5%, it showed Zhitung = 6.17 and Ztabel = 1.65. Because Zhitung > Ztabel, it can be concluded that the learning outcomes of Pancasila Education for class IV of SD Negeri 21 Lubuklinggau after the application of the Contextual Teaching and Learning (CTL) model to the learning outcomes of Pancasila Education for class IV of SD Negeri 21 Lubuklinggau are significantly complete.